Developing probiotic pumpkin juice by fermentation with commercial probiotic strain Lactobacillus casei 431. Issue 3 (25th January 2021) - Dimitrovski, Darko; Dimitrovska‐Vetadjoka, Maja; Hristov, Hristo; Doneva‐Shapceska, Donka
Abstract: Pumpkin ( Cucurbita pepo ) showed to be an excellent source of nutrients for the probiotic growth reaching around 10 10 CFU/ml in just 24 hr. Growth kinetics of the culture was followed during juice fermentation and the Gompertz model was fitted to the data. Approximately 9.6 g/L lactic acid was produced lowering the pH from 6.5 to 3.6 at the end of fermentation. The culture mostly utilized glucose while the fructose was consumed to lesser extent. The survivability test showed that the culture will remain above 10 6 CFU/ml during 13 days of refrigerated storage. Sensory evaluation of the fermented pumpkin juice mixed with other juices showed high acceptance. The principal component analysis revealed three components responsible for the largest portion of the variability within pumpkin juice sensory descriptors. Consensus configuration analysis showed the highest agreement of sweetness, fruity and pleasant smell with samples to which blubbery and fruit juice mix were added. Practical applications: This study represents an original contribution in the field of nondairy probiotic beverages. The research is a comprehensive approach to product development using thorough statistical analysis of data. This is the first time to our knowledge that L. casei 431 is used to ferment vegetable juice.